Huanuco Pampa: Strategic administrative center of the Imperial State of the Incas - Amat Olazával, Manuel Hernán (2015)
This article highlights how the Inca organized, planned strategic spaces for political, economic, religious, military and urban purposes. The great archaeological complex of Huanuco Pampa is one of the most prominent Imperial State administrative centers of the Incas. Spatial planning, in an extensive Andean plateau located in Huanuco region at 3800 meters, evidence his painstaking operation, which is performed rituals and religious ceremonies, the accumulation and redistribution of food stored in hundreds of depots colcas or food, building purposes military called kallankas and powerful means of asserting power and expansive hegemony